Does the South African Physiotherapy Journal fulfill the needs of its constituency? A retrospective article review - J.M. Frantz; I. Diener; J. Jelsma (AOSIS, 2011)
Professional  journals  are  used  to  disseminate  the  knowledge of scholars in the profession and to provide clinicians with guidance for best practice.  This  article  aimed  to  retrospectively  review  the  role  of the  South African  Journal  of  Physiotherapy  and  its  contribution  to  the profession.  An archival  research  design  was  used  to  collect  information from  the  archives of  the  South  African  Society  of  Physiotherapy website.  The  information  was retrieved  using  a  data  capture  sheet and descriptive  statistics  were  used throughout  to  establish  frequencies  for the  relevant  information.  During  the identified period, 170 articles were published. The greatest number of papers originated in South Africa (81%), 8% from the rest of Africa and 11% written by international authors. Authors with a Masters degree contributed almost 50% of the papers and those with doctorates were responsible for at least 25% of the papers. Most of the papers presented original research (81%) with secondary research such as reviews and scholarly papers accounting for 19% of the total. The most common speciality area addressed through research  was  linked  to musculoskeletal  conditions.  The  journal  appears  to  have  provided  an important  platform  for  South African academics and emerging researchers to publish their findings. It is suggested that the journal should give preference to papers that deal with issues that are unique to South Africa and sub-Saharan Africa, as these are the least likely to be published elsewhere. In addition, the journal should emphasise papers that will advance the profession.